Influence of Adhesive Use on Swallowing in Removable Complete Denture Wearers - Oliveira Dantas, Roberto; Rodrigues Montaldi, Marina; Vieira Fortes, Caroline; Barbosa Ribeiro, Adriana; Helena Lovato da Silva, Cláudia (British Journal of Healthcare and Medical Research, 2023)
Background: The objective of conventional complete dentures is to reestablish the functions of the stomatognathic system in edentulous individuals. Adhesives are used for denture retention to help the masticatory function. The objective of this investigation was to evaluate the effect of denture adhesive on the swallowing of complete denture wears. Methods: Nine upper and lower complete denture wearers and 14 individuals with teeth were assessed with videofluoroscopy at 30 frames by second and analyzed frame by frame. The denture wears subjects were assessed without dentures, with dentures without adhesive, and with dentures and adhesive. Duplicate assessments were made with swallows of 10-mL thin-liquid bolus, 10-mL extremely-thick bolus, 5-g cookies, and 2-g toasts. Results: Laryngeal vestibule closure, pharyngeal transit, upper esophageal sphincter opening, and oropharyngeal transit took longer in denture wearers than in controls. Laryngeal vestibule closure time and upper esophageal sphincter opening when swallowing thin liquid were shorter with dentures and adhesive than without adhesive. With extremely thick bolus, the pharyngeal transit time and upper esophageal sphincter opening were shorter with adhesive use. Residues in the oral cavity occurred more frequently in the denture wearers than in the controls, for all boluses. Removable complete denture wearers have longer pharyngeal transit of thin liquid and extremely thick boluses, which decreases with adhesive use. Conclusion: Adhesive use cause a favorable effect on pharyngeal swallowing of thin and thick boluses in complete denture wearers.